The early years : 9th-11th centuries (882-1069) - Plougin, Vladimir (History of Russian intelligence ;, 2001)
Russia's tumultuous early history is unearthed with a view to deciphering the strategies and stratagems that prevailed. Written by best-selling Russian author Vladimir Plougin, a professor at Moscow State University, the stories are drawn from ancient chr.